P1_7 Foetal Ultrasound Imaging Safety in Early Pregnancy - Boadle, Roisin; Wigfield, Emma; Dulay, Amanjit (Physics Special Topics, 2009)
<!–[if gte mso 9]> Normal 0 false false false EN-GB X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0; @font-face font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; mso-fareast-language:EN-US; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> This article discusses the temperature increase of foetal soft tissue due to diagnostic ultrasound scans taken during the early stages of pregnancy. It is found that for standard foetal ultrasound frequencies of 3MHz-5MHz, cell development in the foetal tissue is only affected after scans lasting 600-1000s. Transducer motion is considered and it is demonstrated that the time a small piece of foetal tissue will be exposed to ultrasound heating for is unlikely to be this high. Therefore, it is concluded that there is no danger to the foetus due to heating by standard diagnostic foetal ultrasound imaging.Â